Adjuvanted influenza vaccines. (September 2013) - Even-Or, Orli; Samira, Sarit; Ellis, Ronald; Kedar, Eli; Barenholz, Yechezkel
Influenza is one of the most common causes of human morbidity and mortality that is preventable by vaccination. Immunization with available vaccines provides incomplete protection against illness caused by influenza virus, especially in high-risk groups such as the elderly and young children. Thus, more efficacious vaccines are needed for the entire population, and all the more so for high-risk groups. One way to improve immune responses and protection is to formulate the vaccine with antigen carriers and/or adjuvants, which can play an important role in improving immune responses and delivery to antigen-presenting cells, especially for a vaccine like influenza that is based on protein antigens usually administered without a carrier or adjuvant. In this review, the authors present an overview of available vaccines, focusing on research and development of new adjuvants used in influenza vaccines, as well as adjuvanted influenza vaccines aimed to improve immune responses, protection and breadth of coverage for influenza.